2017
DOI: 10.24884/1682-6655-2017-16-2-75-82
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of mesenchymal stem cells as a tool for studying the mechanisms of stem cell therapy of myocardial infarction

Abstract: Микроинкапсулирование мезенхимных стволовых клеток как инструмент для изучения механизмов клеточной терапии при инфаркте миокарда 1 Северо-Западный федеральный медицинский исследовательский центр им. В. А. Алмазова 194156, Россия, Санкт-Петербург, пр. Пархоменко, д. 15Б 2 Первый Санкт-Петербургский государственный медицинский университет им. акад. И. П. Павлова 197022, Россия, Санкт-Петербург, ул. Льва Толстого, д. 6/8 3 Санкт-Петербургская государственная химико-фармацевтическая академия 197022, Россия, Санкт… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The decidual mesenchymal stem cells isolated have good cell viability, fibroblast-like spiral growth adherent to the wall, and differentiation ability of bone formation and adipogenesis. It was found that our cells separated from decidua meet the minimum MSC standards established by ISCT (International Association for Cell Therapy) [2] and the standards set by the first International Working Group on Placental Stem Cells [19] through immunophenotype by flow cytometry. We found that the high expression of CD146 in the DMSCs isolated in this study (74.7%) was consistent with the results of Dimitrov [18] (Fig S2G ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The decidual mesenchymal stem cells isolated have good cell viability, fibroblast-like spiral growth adherent to the wall, and differentiation ability of bone formation and adipogenesis. It was found that our cells separated from decidua meet the minimum MSC standards established by ISCT (International Association for Cell Therapy) [2] and the standards set by the first International Working Group on Placental Stem Cells [19] through immunophenotype by flow cytometry. We found that the high expression of CD146 in the DMSCs isolated in this study (74.7%) was consistent with the results of Dimitrov [18] (Fig S2G ).…”
Section: Discussionmentioning
confidence: 80%
“…Mesenchymal stem cells (MSCs) are adult stem cells with significant self-renewal ability and multilineage differentiation capacity [1]. MSCs can be isolated from various tissues, including bone marrow, adipose tissue, umbilical cord, and others [2]. Decidua is also an essential source of MSCs [3].…”
Section: Introductionmentioning
confidence: 99%